Equatorial and low‐latitude ionospheric response to the 17–18 March 2015 great storm over Southeast Asia longitude sector. Issue 5 (27th May 2017) - Jiang, Chunhua; Yang, Guobin; Liu, Jing; Yokoyama, Tatsuhiro; Liu, Tongxin; Lan, Ting; Zhou, Chen; Zhang, Yuannong; Zhao, Zhengyu; Komolmis, Tharadol; Supnithi, Pornchai; Yatini, Clara Y.
Abstract: This study mainly investigates equatorial and low‐latitude ionospheric response to a great geomagnetic storm that occurred on 17 March 2015. We found that there were some interesting ionospheric phenomena, e.g., short‐term ionospheric positive effect, daytime spread F, and morning Equatorial Ionization Anomaly (EIA) in the topside ionosphere, emerged at equatorial and low‐latitude region along the longitude of about 100°E. Ground‐based ionosondes and in situ satellite (Swarm) were utilized to study the possible mechanisms for these ionospheric phenomena. We found that vertical downward transport of plasma or neutral induced by traveling ionospheric disturbances (TIDs) or traveling atmospheric disturbances (TADs) might make a contribution to the short‐term ionospheric positive effect at the main stage of this great storm. Additionally, results suggested that the occurrence of daytime spread F at low latitudes might be due to the diffusion of equatorial ionospheric irregularities in the topside ionosphere along geomagnetic field lines. Moreover, observational evidence shows that TIDs also might be the main driver for morning EIA‐like feature recorded by Swarm B satellite in the topside ionosphere. These ionospheric phenomena mentioned above could make us gain a better understanding of ionospheric storm effects at equatorial and low‐latitude region. Key Points: Short‐term ionospheric positive effect was discussed during a great storm Ionosonde observation of daytime spread F was illustrated in this study Morning EIA‐like feature in topside ionosphere was presented during this storm